2022
DOI: 10.2106/jbjs.22.00535
|View full text |Cite
|
Sign up to set email alerts
|

What’s New in Hip Replacement

Abstract: Implant Design and Related Outcomes Dual MobilityDual-mobility cups do not reduce the revision risk for patients with acute femoral neck fracture, as concluded by Rogmark and Nauclér in an observational cohort of 2,242 patients with dual-mobility cups compared with a matched cohort of 6,726 patients treated with a conventional total hip implant 1 . The authors reported that, with implant revision surgery as the outcome, they "could not detect any differences between a total hip arthroplasty with a dual mobilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…When assessing the influence of BMI on bleeding, our study's results were consistent with those of Morgan et al, 23 , 24 , 25 , 26 , 27 , 28 , 34 who reported reduced bleeding with TXA in surgeries. In the case of rhinoplasty, where bleeding levels are not excessively high, dexmedetomidine might be a more suitable option, as indicated by Berenjian et al 21 , 29 , 30 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…When assessing the influence of BMI on bleeding, our study's results were consistent with those of Morgan et al, 23 , 24 , 25 , 26 , 27 , 28 , 34 who reported reduced bleeding with TXA in surgeries. In the case of rhinoplasty, where bleeding levels are not excessively high, dexmedetomidine might be a more suitable option, as indicated by Berenjian et al 21 , 29 , 30 …”
Section: Discussionsupporting
confidence: 91%
“…In terms of blood coagulation factors, Morgan et al 34 found significantly lower bleeding in the TXA group in pelvic fracture surgery, irrespective of patient characteristics. Eftekharian et al 46 observed that TXA significantly reduced bleeding during orthognathic surgery.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Тотальне ендопротезування суглобів нижніх кінцівок стало рутинною протокольною ортопедичною операцією. Авторитетний медичний журнал «Lancet» [1] назвав тотальне ендопротезування кульшового суглоба (ТЕП КС) операцією століття, оскільки вона призвела до революційного поліпшення результатів лікування пацієнтів з остеоартрозом, забезпечуючи відновлення функції суглоба та, відповідно, покращення якості життя на тривалий термін, що зумовило широке застосовування цього оперативного втручання у всьому світі та його постійне технічне вдосконалення [2].…”
unclassified